2009
DOI: 10.1073/pnas.0910351106
|View full text |Cite
|
Sign up to set email alerts
|

F 1 -dependent translation of mitochondrially encoded Atp6p and Atp8p subunits of yeast ATP synthase

Abstract: The ATP synthase of yeast mitochondria is composed of 17 different subunit polypeptides. We have screened a panel of ATP synthase mutants for impaired expression of Atp6p, Atp8p, and Atp9p, the only mitochondrially encoded subunits of ATP synthase. Our results show that translation of Atp6p and Atp8p is activated by F1 ATPase (or assembly intermediates thereof). Mutants lacking the ␣ or ␤ subunits of F1, or the Atp11p and Atp12p chaperones that promote F1 assembly, have normal levels of the bicistronic ATP8/AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 32 publications
3
76
0
Order By: Relevance
“…2D). Similarly, other studies have shown Cox2p to be normally translated in an atp8 null mutant (36). This indicates that formation of Cox2p* is not dependent on the absence of Atp8p.…”
Section: Analysis Of Mitochondrial Gene Products Translated In Vivo Imentioning
confidence: 49%
“…2D). Similarly, other studies have shown Cox2p to be normally translated in an atp8 null mutant (36). This indicates that formation of Cox2p* is not dependent on the absence of Atp8p.…”
Section: Analysis Of Mitochondrial Gene Products Translated In Vivo Imentioning
confidence: 49%
“…Similarly, translation of the Atp6p and Atp8p subunits of ATP synthase on mitochondrial ribosomes is activated by F 1 ATPase or partially assembled F 1 (12). Both regulatory mechanisms achieve a balanced expression of the mitochondrial gene product(s) relative to partner proteins derived from the nucleo-cytoplasmic system.…”
mentioning
confidence: 99%
“…4). Indeed, Atp6 and Atp8 synthesis is dramatically decreased in null mutants of the a (atp1) and b (atp2) F 1 subunits or the Atp11 and Atp12 chaperones required for their assembly (10). The observed translational defect is not owing to transcriptional impairment, mRNA instability or mRNA processing inefficiency as the mature ATP6 and ATP8 mRNAs accumulate at wild-type level in the mutant strains (10).…”
Section: Atp6 and Atp8 Translational Regulationmentioning
confidence: 98%
“…At the beginning of the last decade, a CES mechanism was identified that translationally controls the expression of Cox1 in yeast mitochondria (8,9). More recently, translational regulation of Atp6, Atp8 and Cytb has been also reported (10,11).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation